IMPLEMENTASI KURIKULUM MERDEKA BELAJAR DALAM PEMBELAJARAN IPAS DI SEKOLAH DASAR - Rahman, Rahmania; Fuad, Muhammad (Citra Media Publishing, 2023)
The curriculum plays a major role in the implementation of education at all levels of learning. This research aims to explain and understand the implementation of the independent curriculum in natural and social sciences (IPAS) education in an elementary school. The approach used in this study is descriptive qualitative, with research subjects involving school principals and fourth grade teachers. Data collection methods involve interviews, observation, and documentation. Data analysis involves data reduction, data presentation and drawing conclusions. The research results show that elementary schools have succeeded in implementing the independent curriculum and have been recognized as driving schools. The renewal in the independent curriculum involved science and social studies education which was combined into IPAS. Every semester, science learning is carried out using the method of 2 science chapters and 2 social studies chapters, different from the previous year which divided the semester between science and social studies. This approach is taken to prevent monotonous learning for students. The independent curriculum gives teachers and students freedom in learning, while the science and social studies assessments are combined into IPAS, including in report card assessments